Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/483136
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriIs Not Eradicated after Triple Therapy: A Nested PCR Based Study

Abstract: Detection of Helicobacter pylori after triple therapy is usually carried out by either rapid urease test (RUT), urea breath test (UBT), histology, bacterial isolation, and single round PCR or serological tests. In this study, antral biopsy specimens from 25 patients were tested for H. pylori by RUT, culture, histology, and nested PCR in their antral biopsy specimens before and after treatment. Three genes, namely, heat shock protein (hsp60), phosphoglucosamine mutase (ureC), and flagellar export ATP synthase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…In the current study, a highly conserved gene, HSP60, was targeted to identify H. pylori by nested PCR, which has been proposed as the gold standard test . There was a higher positive rate of H. pylori detected by nested PCR compared with the single‐step PCR and rapid urease tests, in line with the previous study . Fang et al and Siupsinskiene et al found that 39.4% and 32% of vocal polyps cases were H. pylori ‐positive using the rapid urease test, respectively.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In the current study, a highly conserved gene, HSP60, was targeted to identify H. pylori by nested PCR, which has been proposed as the gold standard test . There was a higher positive rate of H. pylori detected by nested PCR compared with the single‐step PCR and rapid urease tests, in line with the previous study . Fang et al and Siupsinskiene et al found that 39.4% and 32% of vocal polyps cases were H. pylori ‐positive using the rapid urease test, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…13,27 There was a higher positive rate of H. pylori detected by nested PCR compared with the single-step PCR and rapid urease tests, in line with the previous study. 14 Fang et al 28 and Siupsinskiene et al 9 found that 39.4% and 32% of vocal polyps cases were H. pylori-positive using the rapid urease test, respectively. Although, in our study, we discovered a low H. pylori-positive rate of 11.4% in vocal fold polyp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only the PCR method allows the detection of even very few bacteria present in specimens of mucosa. Thus, in the study by Patel et al , 4 weeks after eradication with a triple combination drug therapy, H. pylori was detected in only 16% of patients on the histopathological examination and in 12% on the urease test, while the PCR method revealed the presence of the same bacterial strains in as many as 92% of patients [31]. In these patients such an insidious infection can support an inflammatory state then wrongly considered to be H. pylori negative.…”
Section: Discussionmentioning
confidence: 99%